Preventing Murder Without Expanding Punishment: Rethinking Homicide Policy Beyond Deterrence - Zul Khaidir Kadir (Punggawa Law Review, 2026)
This article examines how murder can be prevented without making penal expansion the dominant reflex of criminal policy. The analysis starts from a basic tension in homicide law. Criminal punishment is necessary to condemn intentional unlawful killing, although punishment usually becomes most forceful only after prevention has failed. Using comparative criminal policy analysis, the article compares Japan, Germany, Scotland and England, and the United States to identify how states interrupt lethal violence before murder is completed. The analysis shows that deterrence based on sentence severity has limited preventive value when homicide emerges through coercive control, immediate retaliation, or easy access to lethal means. Japan illustrates the preventive force of strict weapon regulation. Germany highlights the need for legally disciplined early intervention. Scotland and England show how public health and multi-agency strategies can reach serious violence before trial becomes relevant. The United States exposes the weakness of severe punishment where firearm availability remains high and legal trust is uneven. The article advances the concept of homicide prevention architecture, a layered model that links risk intelligence, lethal-means restriction, victim-centred protection, community violence intervention, and accountable criminal law while preserving legality, proportionality, and culpability. This approach simultaneously resists punitive reflex and preventive overreach.